APPLICATION OF DETERMINISTIC MODEL FOR HYPERTENSION CASES - Dalengkade, Mario Nikolaus; Hayati, Martina; Pujiastuti, Dwi Rahayu (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
World Health Organization (WHO) latest reports about hypertension as a global health problem, due to a spike in cases. One of the roles of mathematics in health is to provide information about the increase in hypertension sufferers. Using a deterministic model is supposed to provide information that can explain how the cases increase. The deterministic model used is divided into two equations. The first equation uses k as a constant. Second, is p for p < 1 and p > 1. The results from both equations are in the form of a logistic curve and show simulation results are similar to condition data for hypertension sufferers. In addition, the extended deterministic model with p <1 indicates that hypertension sufferers increase exponentially, thus an intervention step is needed.